A Study of Supply Chain Management Aspects of Village Owned Enterprises in Indonesia - Sulastriyono Sulastriyono; Jumadil Saputra (International Journal of Supply Chain Management, 2020)
Abstract. Supply chains depend on community resources such as entrepreneurs, natural resources, and facilities in value creation and successful operation, while communities need development opportunities from supply chains to build and maintain prosperity. The mutual influence between supply chains and communities offers opportunities to integrate sustainability initiatives into the chain. Village Owned Enterprises is the village financial institutions has been regulated by the government since the colonial era to the present. It gives an opportunity for villages to prepare themselves in an effort to establish Village Owned Enterprise accordance with local potential both human and natural resources owned by the village. The Village Law provides an opportunity for villages so that Village Owned Enterprise can be one of the tools of the struggle for economic improvement and welfare though the sustainable supply chain. The challenges of the establishment and business development of Village-Owned Enterprise are increasingly complex. This is because not all villages in Indonesia are ready with adequate human resources in making village regulations, looking for business opportunities, being administrators, making reports and implementing Village-Owned Enterprise supply chain management. The interactions among the supply chains and communities provide significant insights into how to create sustainability for both.